Custo e ganho da dívida e as conexões políticas: um estudo em empresas listadas na bm&fbovespa - Santos, Ana Karoliny Apolinário (2017)
This study sought to analyze the effect of the political connections on the cost and the corporate debt gain, assuming the importance of the benefits tied to the government's political interference in the firms. Based on the model proposed by Bliss and Gull (2012), the political connections were measured in a way adapted to the Brazilian context, following three means in which the government uses to maintain links with the organizations, they are: the connection by property structure , By board of directors and by donations or financing to the electoral campaigns. The sample consisted of 233 companies that had their cost and their debt gain quantified, verified the possible relations with the political connections and some financial characteristics, through regressions by the Weighted Least Squares Method (MQP), a methodology that seeks to assign a lower Weight to the observations that have greater variance of the error. In the results it was possible to observe, from the descriptive analyzes, a median of the debt cost per year of 16.72. It can also be observed that the effective gain of the debt, from the reduction of its cost, is not enjoyed by all the companies in the sample. Based on the regression analysis, it can be observed that the companies that hold the government ownership, with the direct shareholding in their shareholding structure, have a reduced debt cost in relation to the other companies in the sample. In addition, the evidence indicates that companies that have members of their Boards of Directors with political backgrounds earn higher debt gains. Thus, it is possible to emphasize that the main contributions of this study refer to the evidence that the political connections of companies in Brazil are directly related to the reduction of the cost of corporate debt, which is also confirmed by the study of their positive relations With the debt gain, since it is possible to notice that politically connected companies have a greater reduction of their cost of debt than their cost of equity. This suggests that such firms may be having greater access to the reduced interest rates of public banks.